ASSESSING THE ECONOMIC BENEFITS OF FOREST CARBON RESERVOIRS IN VIETNAM: IMPLICATIONS FOR FOREST CARBON TRADING MARKET DEVELOPMENT - Duong Thi Thanh; Zhang Ying; Than Thi Huyen; Nguyen Thi Thanh Nguyen (Journal of Animal and Plant Sciences, 2024)
The forest carbon sink is a cornerstone in Vietnam's strategy to combat climate change, aiming for carbon neutrality by 2050 as pledged during COP26. Assessing the economic benefits of Vietnam's current forest carbon sinks is crucial for initiating a domestic forest carbon trading market. Following protocols set by the Inter-Ministerial Committee on Climate Change in 2006, market valuation techniques to approximate the economic value of the forest carbon reservoir were employed. Results show Vietnam's forest ecosystems sequester about 1,401.52 million tons of carbon, equivalent to 5,143.60 million tons of CO2. The estimated economic value is approximately 25,717.95 million USD, with natural forests valued at about 87.44 million USD annually and planted forests at 63 million USD annually. These findings underscore Vietnam's capacity to establish and expand its forest carbon trading market. However, currently the establishment of Vietnam's forest carbon sink market is still in the preparatory phase and has not yet developed into an independent and complete trading system. Therefore, to optimize this potential, Vietnam needs to improve forest quality, promote sustainable forestry economics, and conduct scientific research to provide persuasive and reliable evidence, to support policies for the establishment and development of the forest carbon sink market.
Keywords: Biomass; economic value; forest carbon sink; market value method; stock volume; Viet Nam